Ressonância magnética com imagem de tensor de difusão e espectroscopia na avaliação dos focos de hipersinal na ponderação T2 no encéfalo em crianças e adolescentes com neurofibromatose tipo 1 - Ferraz Filho, José Roberto Lopes (2011)
Neurofibromatosis type 1 (NF1) in children and adolescents is frequently associated with the appearance of focal lesion hyperintensities on T2-weighted images seen in the brain which are called Unidentified Bright Objects (UBOs). These lesions are not an accepted criterion in the diagnosis of NF1 and the exact nature of UBOs remains unclear. Objectives: article 1: This study employed diffusion tensor imaging (DTI) to evaluate the relation among fractional anisotropy (FA) patterns with the findings of T2 sequences in individuals with NF1; article 2: To evaluate the evolution of UBOs in individuals with NF1 by serial MRI, and to relate this to regional fractional anisotropy (FA); article 3: To evaluate the metabolic patterns by magnetic resonance spectroscopy (MRS) of the brain, in the presence of UBOS in patients with NF1. Methods: article 1: Forty-four individuals with NF1 and 20 control subjects were evaluated. The comparative analysis of FA between NF1 and control groups was based on four pre-determined anatomic regions of the brain and related to the presence or absence of UBOs; article 2: The signal pattern of the T2-weighted sequences in the basal ganglia, thalamus, brain stem, and cerebellum for 27 NF1 individuals and a control group were analyzed by DTI. The presence or absence of UBOs in 2 consecutive MRI examinations were related to FA. article 3: Forty-two individuals with NF1 and 25 control subjects were evaluated by examination of ERM univoxel placed in the region of the globus pallidus. Automated quantitative analysis was made of the relationship of the metabolites choline/creatine (Co / Cr), N-acetyl aspartate/creatine (NAA / Cr) and myoinositol/creatine (MI / Cr) and related to the occurrence of UBOS in region of the globus pallidus. Results: article 1: The FA values between the groups demonstrated statistically significant differences (p ≤ 0.05) for the cerebellum and thalamus in NF1 patients, independent of the occurrence of UBOs; article 2: We demonstrated statistically significant differences in FA for the basal ganglia, cerebellum, and thalamus between NF1 patients and controls (P ≤ 0.05), even with a reduction or disappearance of UBOs; article 3: We demonstrated statistically significant differences between of patients with NF1 and control groups as the average values Mi/Cr and Co/Cr (P<0.05) in the region of the globus pallidus. Conclusions: article 1: MR imaging using DTI technique suggests that UBOs are due to microstructural defect of the brain tissue in NF1 patients. article 2: MRI allows for adequate monitoring of the temporal and spatial distribution of UBOs in patients with NF1. DTI confirmed changes in FA despite the disappearance or reduction of UBOs. article 3: MR spectroscopy allows the characterization of the tissue abnormalities not demonstrable in the conventional MR sequences of patients with NF1 by analysis of metabolites Co and Mi.